Tasybīh dalam Puisi “Bānat Su‘ād” Karya Ka’b bin Zuhair - Naf'an, Abdul Wahhab (Adabiyyāt: Jurnal Bahasa dan Sastra, 2016)
Poem "Bānat Su'ād" is a masterpiece by the poet of Ka’b bin Zuhair. The Poem was delivered directly in front of The Prophet Mohammad. This article aims at exploring the elements of tasybīh in the poem. The poet uses tasybīh in expressing his feelings about Su'ād, nāqah, The Prophet Mohammad., muhajirin and the unbelievers. This research breaks down the elements of beauty in this poetry. It can be concluded that the exposure through the used forms tasybīh, the poet really managed to achieve the goals/ Garaḍ of his poetry marked with the provision of forgiveness from The Prophet Mohammad. That is why, the poem was awarded a burdah directly by the The Prophet Mohammad.